2014
DOI: 10.1515/jelf-2014-0017
|View full text |Cite
|
Sign up to set email alerts
|

Mutual face preservation among Asian speakers of English as a Lingua Franca

Abstract: This study identifies strategies used by speakers of ELF from AsiaPacific countries for managing rapport in response to potentially facethreatening utterances in informal, non-hierarchical situations. The analysis, which draws on the Asian Corpus of English (ACE), reveals numerous points of contact with existing studies of English as a lingua franca. Potentially facethreatening utterances were usually -though not always -countered with a move to normalise the flow of conversation and maintain interactional rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…He prefaces his turn with a single laughter particle and the discourse marker "okay"hearable as signalling a supportive, cooperative stance toward a previous speaker's message (House 2013b). (In fact, this discourse marker has been shown elsewhere to serve a conciliatory function in ACEsee Walkinshaw and Kirkpatrick 2014). He then employs jocular sarcasm (Attardo 2002;Dynel 2009;Jorgensen 1996), thanking the producer as though she had complimented him on some positively valenced character trait.…”
Section: Jocular Agreement With Negative Self-assessmentmentioning
confidence: 95%
See 2 more Smart Citations
“…He prefaces his turn with a single laughter particle and the discourse marker "okay"hearable as signalling a supportive, cooperative stance toward a previous speaker's message (House 2013b). (In fact, this discourse marker has been shown elsewhere to serve a conciliatory function in ACEsee Walkinshaw and Kirkpatrick 2014). He then employs jocular sarcasm (Attardo 2002;Dynel 2009;Jorgensen 1996), thanking the producer as though she had complimented him on some positively valenced character trait.…”
Section: Jocular Agreement With Negative Self-assessmentmentioning
confidence: 95%
“…The third characteristic which I will outline here is House's (2013a) assertion that ELF speakers consistently demonstrate solidarity and consensus, despite their differing linguistic and cultural backgrounds. One aspect of this apparent solidarity orientation is that when some action occurs which is construable as threatening to interactional rapport, the participants promptly move to normalise the conversation so that it can continue along its prior trajectory (Walkinshaw and Kirkpatrick 2014). Actually, a clarification is needed here: recent research into situated, task-focused exchanges such as business meetings (Bjørge 2012;Jenks 2012;Pullin Stark 2010), courtrooms (Kirkpatrick et al 2016), or interactions between immigration officials and asylum seekers (Guido 2012) suggests that solidarity orientation is context-dependent and may be de-prioritised in favour of achieving interactional goals.…”
Section: English As a Lingua Francamentioning
confidence: 99%
See 1 more Smart Citation
“…Habib's (2008) study of humour and disagreement among female ELF users in the US found that humour (particularly jocular teasing) and disagreement were used to maintain and display interactional rapport among interactants (cf. Walkinshaw, 2016;Walkinshaw and Kirkpatrick, 2014). Rogerson-Revell (2007) and Moody (2014) 10.1163/26660393-bja10010 | Contrastive PragmaticS (2020) 1-29 highlight a similar function in business contexts in South East Asia and Japan respectively.…”
Section: 4mentioning
confidence: 99%
“…In this study I seek to contribute to the growing body of work exploring the pragmatic aspects of ELF -a line of research that can be traced back to Meierkord's pioneering work published two decades ago (Meierkord 1996). Recent empirical studies of ELF pragmatics have addressed a broad range of issues, including the use of stance markers and other discourse markers to express intersubjectivity (House 2013, Pullin 2013, face preservation strategies used in ELF interaction (Walkinshaw and Kirkpatrick 2014), disagreement among ELF speakers (Maíz-Arévalo 2014), and vagueness (Metsä-Ketelä 2016); a synthetic overview of the development of ELF pragmatic research is given in Kecskes (2013).…”
Section: Introductionmentioning
confidence: 99%